Plant extracts as biostimulant agents: a promising strategy for managing environmental stress in sustainable agriculture - Han, Mingzhao; Kasim, Susilawati; Yang, Zhongming; Deng, Xi; Saidi, Noor Baity; Uddin, Md Kamal; Mohd Shuib, Effyanti (Tech Science Press, 2024)
It is imperative to enhance crop yield to meet the demands of a burgeoning global population while simultaneously safeguarding the environment from adverse impacts, which is one of the dominant challenges confronting humanity in this phase of global climate change. To overcome this problem and reduce dependency on chemical fertilizer, scientists now view the implementation of biostimulant strategies as a cost-effective and environmentally friendly approach to achieving sustainable agriculture. Plant extracts are rich in bioactive phytocompounds, which can enhance plant resistance to disease, pest, and abiotic stresses (e.g., drought, salinity, and extreme temperature), and promote plant growth and productivity. Furthermore, the application of plant extracts through soil drenching can also significantly change the rhizosphere soil microbiome, and indirectly interact with plants, eventually stabilizing plant growth. Currently, the application of plant extracts as a whole is effective, which emphasizes the contribution of complex interactions between multiple compounds, with seaweed extracts being the most widely studied and utilized. Interestingly, plant extracts are compatible with fertilizer and can be applied in conjunction with nutrient inputs to further enhance their effectiveness. Given all this knowledge, exploring the growth and functional effects induced by plant extracts, as well as understanding their interactions and mechanisms in plants, is crucial for developing advantageous approaches with potential value in integrated crop management systems, ultimately contributing to sustainable production.